From the Vault to the Road: The Paradigm of the Itinerant Museum in the Democratization of Natural Heritage - Sánchez-Ocampo, Marcela (Advances in Social Sciences Research Journal, 2026)
Natural history museums serve as critical infrastructures for both academic research and public scientific literacy. However, the centralization of these institutions in urban hubs creates significant barriers to access for rural and marginalized communities, limiting the democratization of natural heritage. This article examines the operational "anatomy" of traditional museums, detailing the rigorous conservation requirements for diverse taxonomic collections—from entomology to paleontology—and the evolution of immersive museography. Building upon these foundations, we propose a paradigm shift toward the itinerant museum model. By analyzing the logistical precedents of historical traveling circuses and modern mobile health units, we argue that modular, climate-controlled mobile infrastructures can replicate the preservation standards of static institutions. The study delineates strategies for selecting robust "itinerant specimens" (e.g., resin inclusions, high-fidelity replicas) and engineering adaptive exhibition spaces using inflatable structures and flight-case systems. Ultimately, this framework posits that mobile museums can effectively decentralize biological knowledge without compromising scientific rigor.